(untitled) (Communications in Mathematical Research, 2019)
In this paper we discuss stochastic differential equations with a kind of periodic boundary value conditions (in sense of mean value). Appealing to the decomposition of equations, the existence of solutions is obtained by using the contraction mapping principle and Leray-Schauder fixed point theorem, respectively.